Multi-User Expert System for Operation and Maintenance in Energized Lines. - Moreno Iza, Erika Fernanda (2019)
The article presents the development of a multi-user application in vir-tual reality for the training and theoretical-practical training of electrical mainte-nance personnel in the operation of energized lines. The environment has a safety explanatory room in which users will know each of the rules and protocols ap-plied to perform maintenance maneuvers and operation of energized lines, a re-alistic work area of the electrical power system that starts from hydroelectric gen-eration and passes through transmission lines, subtransmission to reach substa-tions that raise or reduce the voltage for subsequent distribution. The environ-ment has been created using photogrammetry techniques, WorldComposer, CAD design tools, Unity 3D, DigSilent Power Factory and Matlab to provide realism of electrical system behavior, emulating failures and critical conditions caused by external and internal emergency events. Experimental tests show the effi-ciency of the system generated by human-machine interaction in which operators interact between themselves and the ambience, facilitate immersion in an envi-ronment that offers to contribute to the development of their risk-free collabora-tive skills and abilities.